2019
DOI: 10.3390/genes10100811
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Insight into Gibberellin- and Jasmonate-Mediated Stamen Development

Abstract: In flowering plants, proper development of male generative organs is required for successful sexual reproduction. Stamen primordia arise in the third whorl of floral organs and subsequently differentiate into filaments and anthers. The early phase of stamen development, in which meiosis occurs, is followed by a late developmental phase, which consists of filament elongation coordinated with pollen maturation, anther dehiscence and finally viable pollen grain release. Stamen development and function are modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 105 publications
(226 reference statements)
3
48
0
Order By: Relevance
“…Plant hormones, including auxin, cytokinin, and ethylene, have a lasting impact on regulating plant architecture and development [39]. In order to explore the possible functions of OsDUF668s in response to hormone stress, we used qRT-PCR to analyze their relative expressions under 6BA, IAA, GA, SA, and ABA treatments (Figure 4).…”
Section: Expression Profiles Of Osduf668s In Response To Plant Hormonementioning
confidence: 99%
“…Plant hormones, including auxin, cytokinin, and ethylene, have a lasting impact on regulating plant architecture and development [39]. In order to explore the possible functions of OsDUF668s in response to hormone stress, we used qRT-PCR to analyze their relative expressions under 6BA, IAA, GA, SA, and ABA treatments (Figure 4).…”
Section: Expression Profiles Of Osduf668s In Response To Plant Hormonementioning
confidence: 99%
“…Histological analyzes became necessary, which made it possible to identify the moment of anther dehiscence, pollination, fertilization, pod and seed setting, as well as their early and late development. In many species, late anther/stamen development is defined as a stage that occurs after the opening of the flower [58,59]; however, in various lupines there is a phenomenon called kleistogamy, in which dehiscence occurs before flower opening, leading to self-pollination. Under natural conditions, most annual lupines are self-compatible and mainly reproduce by self-pollination.…”
Section: Self-pollination Occurs When Flowers Are Closed Followed By mentioning
confidence: 99%
“…The Arabidopsis GA biosynthesis and perception mutants such as ga1-3, gid1a-1 gid1b-1 gid1c-1 are male sterile due to unelongated filament, and delayed anther development [4]. Previous studies showed that GA increases the expression of the JA biosynthesis gene DAD1 to promote JA biosynthesis, and activates the expression of MYB21, MYB24, and MYB57 to mediate filament elongation [47].…”
Section: Della Proteins (Gibberellic Acid Insensitive [Gai] Repressomentioning
confidence: 99%